The Challenges and Opportunities of Implementing a Cambridge Primary Curriculum in Local Schools: A Qualitative Case Study of Linguistic and Cultural Negotiation at SD Muhammadiyah 3 ICP Sumberrejo - Muryanti; Estu Widodo; Santi Prastiyowati (Journal of Educational Studies, 2026)
This study explores the implementation of the Cambridge Primary Curriculum in a faith-based primary school context at SD Muhammadiyah 3 ICP Sumberrejo, Bojonegoro, Indonesia. The research focuses on how international curriculum standards are negotiated within local linguistic, cultural, and religious realities, particularly through English-Medium Instruction (EMI). Employing a qualitative approach with a critical ethnographic design, data were collected through four techniques: in-depth interviews, classroom observations, document analysis, and focus group discussions involving teachers, students, parents, and school administrators. The findings reveal that the integration of the Cambridge curriculum with Muhammadiyah Islamic values and Javanese local wisdom has produced a hybrid educational model that is both adaptive and contextually grounded. The study further shows that EMI functions as a dynamic site of linguistic and cultural negotiation. Teachers play a central role as mediators by employing strategic code-switching, bilingual scaffolding, contextual translation, and localized material adaptation to support students’ conceptual understanding. These practices enable students to engage with global knowledge while maintaining cultural and religious rootedness. This study contributes theoretically to discussions on curriculum internationalization by emphasizing the importance of linguistic negotiation within curriculum hybridity. The findings highlight that successful international curriculum implementation in local faith-based schools depends not only on structural integration but also on culturally and linguistically responsive pedagogical practices